Strategi Pemasaran Holistik Starbucks dari Cangkir ke Komunitas - Ni Nyoman Retno Arthasa; Asep Saefurahman (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This research aims to analyze the holistic marketing strategy implemented by Starbucks, focusing on the approach from